Western European Intellectual Practices of a New Type in Russian Everyday Life at Early 18th Century (case of Feofan Prokopovich) - I. Yu. Khruleva (Vestnik MGIMO-Universiteta)
The focus of this study is the views of Feofan Prokopovich, a unique Orthodox thinker whose world outlook was shaped by an obvious influence of the ideas of the Protestant and Catholic Enlightenment. Talking about the Enlightenment, modern historiography focuses on the versatility of the phenomenon, preferring to talk about the Enlightenment, including the religious or confessional Enlightenment, aimed at rethinking the role of religion and the church. The Religious Enlightenment was a pan-European phenomenon that embraced Protestantism, Catholicism, Judaism, and Orthodoxy, and grew out of the desire to create an intelligent religion free of superstition and serving society. The intellectual movement of the religious Enlightenment sought to reconcile the natural philosophy of the 17th-18th centuries with a religious worldview, while trying to overcome the extremes of religious fanaticism, on the one hand, and nihilism and godlessness, on the other. The process of forming a new intellectual environment is marked by the coexistence and mutual influence of the most diverse, sometimes poorly compatible traditions, their transformation and modification. Comprehensively arguing the need for unlimited autocracy in Russia, Feofan Prokopovich, nevertheless, actively used the discourse of the Enlightenment in his writings, discussing the problem of the origin of the state, the mode of government, the boundaries of the power of the monarch, the rights and duties of subjects. On the example of Feofan Prokopovich, we can talk about the emergence and rooting of intellectual practices of a new type in Russian everyday life. The integration of Western European ideas and practices into Russian culture was ambiguous, multifaceted and depended on their adaptation to the socio-political space of Russia. Being well acquainted with the works of European authors of the 17th early 18th centuries, he rather took on the formal side of their discussions on socio-political topics, adapted a conceptual glossary that was new for the Russian educated public, which opened up opportunities for talking about politics in a new way.